Hacking exposed 7 : network security secrets & solutions - McClure, Stuart; Kurtz, George; Scambray, Joel (McGraw-Hill, 2012)
High-profile viruses and hacking incidents serve to highlight the dangers of system security breaches. This revised text provides network administrators with a reference for implementing and maintaining sound security policies